Efficacy and safety of guselkumab in patients with psoriasis who have an inadequate response to ustekinumab: results of the randomized, double‐blind, phase III NAVIGATE trial. (1st January 2018) - Langley, R.G.; Tsai, T.‐F.; Flavin, S.; Song, M.; Randazzo, B.; Wasfi, Y.; Jiang, J.; Li, S.; Puig, L.
Summary: Psoriasis is a chronic disease causing red and scaling skin lesions. Current treatments, especially biologics, which are either given by injection or intravenous infusion (IV), are very effective in the treatment of moderate to severe plaque psoriasis. However, most patients look to achieve clear skin, so there is room for improvement. One approved biologic, ustekinumab, blocks two of the body's internal proteins, interleukin (IL)‐12 and IL‐23. Blocking these proteins prevents signals that cause inflammation in psoriasis. While ustekinumab is effective in many patients, most will not achieve complete skin clearance. Because recent scientific evidence shows that IL‐23 may be more important than IL‐12 in causing psoriasis, guselkumab, a new treatment that specifically targets IL‐23, but not IL‐12, has been developed and was recently approved in the U.S. to treat moderate to severe psoriasis. In the NAVIGATE trial, 871 patients with moderate‐to‐severe plaque psoriasis received ustekinumab and if, after 16 weeks, patients were not clear or almost clear, they were randomly assigned to either continue ustekinumab or start treatment with guselkumab until week 44. From week 16 until week 40, the average number of visits (maximum = 4) at which patients were clear or almost clear was significantly greater in patients treated with guselkumab (1.5) than with ustekinumab (0.7). In addition, at week 28, twice the proportion of patients on guselkumab (31.1%) were clear or almost clear than on ustekinumab (14.3%). Infections were the most commonly reported adverse event among patients on either guselkumab or ustekinumab. The authors conclude that for patients who do not achieve clear or almost clear skin after ustekinumab treatment, switching to guselkumab could be an effective treatment strategy and did not raise safety concerns.